Reporting a Rural Reality: A Case Study of an Agricultural Newspaper’s Series on the Rural Opioid Epidemic - Cara R. Lawson; Courtney Meyers; Amy Boren; Erica Irlbeck; Amber McCord (Journal of Applied Communications, 2022)
Opioid drug abuse has created an epidemic recognized as a public health emergency in 2017, and the detrimental impacts of this epidemic have reached into rural America. When it comes to presenting information via the mass media, communications professionals serve as gatekeepers for what information is passed on to media consumers. Additionally, news organizations place certain degrees of importance upon issues through the amount of coverage dedicated to an issue. In late 2016, when the Farm and Dairy newspaper editorial staff decided to dedicate a vast amount of time and resources to covering Ohio and Pennsylvania’s rural opioid epidemic, a variety of questions and concerns followed. This complicated topic was largely unfamiliar and untraditional to agricultural communications. Concerns about how to research the topic, work with sources, and manage responses from stakeholders emerged at the onset, but motivations to increase awareness, reduce stigma, and instill hope in the midst of a rural opioid epidemic brought the series to fruition. This case study details the actions taken by those involved in the series and stakeholder reactions to a unique journalistic investigation from a rural newspaper. Discussion of recommendations for future research and curricular impacts are provided.
Keywords: case study; qualitative; rural health; newspaper; opioid